La innovación en el transporte de quito: pasado, presente y desafíos futuros - Tellería Buitrón, Gustavo Alejandro (2025)
This article explores the evolution and current challenges of the transportation system in San Francisco de Quito, the capital of Ecuador, highlighting how innovation has been a constant throughout its history. Despite topographical and urban planning difficulties, Quito has managed to implement significant mobility solutions, which have served as a model for the region and improved the quality of life of its inhabitants. Through a comprehensive documentary review, this study analyzes the city's founding to the inauguration of Metro Line 1, revealing the crucial role of public transport policies and management in addressing vehicular congestion, population mobility, and air quality. While Quito's population and reliance on the private vehicle continue to grow, the urgency of transportation policies and practices that prioritize accessibility, efficiency, and environmental sustainability is discussed. Quito's transportation innovation illustrates a path towards a more accessible and sustainable urban future, demonstrating the city's dynamism and resilience in the context of its urban development.